2018
DOI: 10.1126/sciadv.aav2131
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of FACT removal from transcribed genes by anticancer drugs curaxins

Abstract: Protumor factor FACT is removed from transcribed genes by anticancer drugs curaxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 63 publications
(163 reference statements)
5
61
0
1
Order By: Relevance
“…To further investigate whether Ssrp1 represses other genes or TEs in ESCs, we analyzed the transcriptome of Ssrp1 −/− ESCs by RNA-seq. Surprisingly, more genes were upregulated (895 genes) than downregulated (213 genes) after the loss of Ssrp1 (Figure 3A and Supplementary Table S2 ), although Ssrp1 is traditionally associated with actively transcribed genes ( 53 ). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of Ssrp1 target genes identified downregulation of various cellular metabolic pathways related to the biosynthesis of amino acids, antibiotics and glycolysis whereas upregulated KEGG terms were enriched of pathways related to cell cycle, p53 signaling, viral infection and ubiquitination (Figure 3B and C ).…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate whether Ssrp1 represses other genes or TEs in ESCs, we analyzed the transcriptome of Ssrp1 −/− ESCs by RNA-seq. Surprisingly, more genes were upregulated (895 genes) than downregulated (213 genes) after the loss of Ssrp1 (Figure 3A and Supplementary Table S2 ), although Ssrp1 is traditionally associated with actively transcribed genes ( 53 ). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of Ssrp1 target genes identified downregulation of various cellular metabolic pathways related to the biosynthesis of amino acids, antibiotics and glycolysis whereas upregulated KEGG terms were enriched of pathways related to cell cycle, p53 signaling, viral infection and ubiquitination (Figure 3B and C ).…”
Section: Resultsmentioning
confidence: 99%
“…Indirect inhibition of the FACT histone chaperone is the most well-studied activity of the curaxins 27,28,47 . Curaxin binding to DNA induces nucleosome destabilization genome-wide 27,47 , which, in turn, generates superhelical tension that cannot be relieved due to topoisomerase inhibition and induces B- to Z-DNA transitions 27 . During this process, multiple epitopes within the destabilized nucleosome become available for FACT binding.…”
Section: Discussionmentioning
confidence: 99%
“…After confirming the oncogenic function of FACT complex, we tested the therapeutic potential of Curaxin that binds to DNA, thereby trapping FACT complex in chromatin 29. We showed that HCC cells were highly sensitive to Curaxin treatment, whereas immortalised hepatocyte line MIHA was more tolerant to Curaxin compared with HCC cell lines (figure 8A,B), indicating that Curaxin selectively suppressed cancer cell growth.…”
Section: Resultsmentioning
confidence: 89%